Max White - White, M (The University of Auckland Fine Arts Library, 2011)
This publication grew out of the exhibition "components of a special collection: a collaboration with the University of Auckland Fine Arts Library" at projectspace B431 from March 31 to April 09, 2011. The exhibition was formed from a desire, firstly to make the Library's collection of artists books available as a public display and secondly to identify themes in the collection and open them up to theoretical analysis. Rather than define the collection, the methodology of the project sought to unpack its possibilities. My written contribution to this catalogue (artist book) followed the authors' request for responses to five specific questions asked of every contributor.
Keywords: Artist book